Narasi Alam Dan Perempuan Dalam Cerpen Pilihan Kompas Edisi 2025 - Aldi Firnanda; Zainuri Ihsan; Mila Ayu Sri Wardani; Agik Nur Efendi (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
Environmental and gender issues are two urgent and interconnected problems. Exploitation of nature often goes hand in hand with the oppression of women, especially in patriarchal and capitalist systems. Therefore, it is important to examine the literary work in the form of selected short stories from the 2025 edition of Kompas, which represents this interconnectedness. Literature is considered relevant because it serves not only as entertainment but also as a medium for social criticism and ecological reflection. The research methodology uses a descriptive qualitative approach with a content analysis design. Primary data consists of short stories published in Kompas in 2025, while secondary data is obtained from theoretical books and scientific articles. Data collection techniques were carried out through documentation, reading, note-taking, and text classification, which were then analyzed using an ecofeminist perspective. The research examines how the relationship between women and nature is represented in short stories. By identifying narratives that feature symbols, metaphors, and events linking gender oppression with ecological damage. The study results show that women are depicted as both a marginalized group and agents of resistance, while nature is positioned as a neglected entity. Ecofeminist analysis reveals that the exploitation of women and nature both stem from the logic of patriarchal domination and capitalism. This research not only demonstrates the relevance of gender and environmental issues in literary texts but also makes a significant contribution to the study of contemporary Indonesian literature by introducing an ecocriticism-feminism perspective as a new lens for understanding the social, cultural, and ecological dynamics manifested in contemporary literary works.